Empowering students in network security : A web-based learning strategy with the arcs model - Ng, Chun Yap (2025)
According to nowadays, technology has become more advanced in the world. In Malaysia it also becomes the hot topic between the society. With the advancement of technology, people find out that technology is a double-edged sword to our society. Especially for students, they need to know how to protect themselves in network. It brings out that network security is a critical skill for students nowadays. However, the traditional methods of teaching network security lack engaging content and are expensive. This project proposes a website which uses the ARCS model that can teach students network security concept in a more efficient and affordable way. The website will include PowerPoint slides, quizzes, video about hands-on labs and tutorials that will help students learn the essential skills they need to protect themselves online and gain new knowledge. Not only that, but the website will also have some mini games which will further enhance engagement and reinforce key concepts for students when they are playing it. The website also can help the students to reduce learning time. In summary, this project is to enhance the student to be aware of the problem about network security. Students also can learn how to protect their personal privacy when using the network and let the student know how they can solve it if they face the network security problem.